Electro-architected porous platinum on metallic multijunction nanolayers to optimize their optical properties for infrared sensor application. (2nd February 2018) - Stanca, Sarmiza Elena; Hänschke, Frank; Zieger, Gabriel; Dellith, Jan; Dellith, Andrea; Ihring, Andreas; Belkner, Johannes; Meyer, Hans-Georg
Abstract: Tailoring the physicochemical properties of the metallic multijunction nanolayers is a prerequisite for the development of microelectronics. From this perspective, a desired lower reflectance of infrared radiation was achieved by an electrochemical deposition of porous platinum in nonaqueous media on silver mirror supported nickel–chrome and nickel–titanium metallic films with incremental decreasing thicknesses from 80–10 nm. The electro-assembled architectures were examined by means of scanning electron microscopy and Fourier transform infrared spectroscopy and it was observed that the layer and sublayer thicknesses and resistivities have a substantial effect upon the porous platinum morphology and its optical properties. It is here reported that the augmentation of the metallic layer electrical conductivity determines the electroformation of more compact platinum nanolayers. Moreover, the platinum black coating of metallic nanolayers causes a considerable decrease of the reflectance in the region from 1000–8000 cm −1 .